Ikonis Budaya dalam Novel Tiba Sebelum Berangkat Karya Faisal Oddang ( Tinjauan Semiotika Charles Sanders Pierce) - Rismawati Rismawati; Muhammad Rapi; Juanda Juanda (Indonesian Journal of Social and Educational Studies, 2021)
Abstract. This study aims to describe the cultural aspects in terms of symbols in Faisal Oddang's Tiba Before Berangkat novel with a study of the semiotic theory of Charles Sanders Pierce. This research is a descriptive qualitative research type. The data source for this research is the novel Arrive Before Departure by Faisal Oddang published by PT Gramedia, Jakarta in 2018 with a thickness of 216 pages. The data of this research are quotations containing cultural aspects in terms of symbols obtained from the novel Tiba Before Berangkat by Faisal Oddang based on a review of Charles Sanders Pierce's semiotic theory which consists of 3 signs. The data were collected using library techniques and analyzed by following the reduction steps, including presenting the data, concluding and verifying the data. The results showed that the cultural aspect in terms of symbols is contained in Faisal Oddang's novel Tiba Before Berangkat. Keywords: Culture, Icon, Novel.